Memahami Konsep Kompetensi Karyawan Sebagai Bagian dari Perencanaan SDM - Marhamah Izat Rodliyah; Musliyana Musliyana; Sunarti Sunarti (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2024)
Human resources as a resource in a company have a strategic role compared to other resources. Humans play a very important role in the development of a company. If a company has higher quality human resources than its competitors, then its performance will definitely increase. Human resource and competency planning in a company plays an important role in improving human resources, especially in terms of employee performance, employee performance to help achieve company goals. In this case, employee performance is a result that can be achieved by an individual or group of people in a company organization according to quantitative or qualitative aspects, considering employee compensation. Apart from that, a mismatch between an employee's competency (the employee's educational background and skills) and their job can also make the employee uncomfortable with what they are doing. This of course greatly affects the level of work productivity in the company. Competencies can clarify work standards and expectations that the company wants to achieve and can make it easier for companies to align work behavior with organizational values. Apart from that, HR planning as an activity is a process of how to meet current and future workforce needs for an organization. In meeting current workforce needs, the HR planning process means efforts to fill/cover workforce shortages both in quantity and quality. HR planning emphasizes forecasting efforts regarding workforce availability based on needs in accordance with future business plans.